Efficacy of Face-to-Face Delivered Cognitive Behavioral Therapy in Improving Health Status of Patients With Insomnia: A Meta-Analysis - Xu, Dawei; Cardell, Elizabeth; Broadley, Simon A.; Sun, Jing (Frontiers in Psychiatry, 2021)
Abstract Background Face-to-face cognitive behavioral therapy (CBT) is one of the most widely used non-pharmacological treatment approaches for insomnia. The aim of this study is to assess the efficacy of face-to-face delivered cognitive behavioral therapy on health outcomes and to evaluate the effect of CBT components as subgroup variables to explain the efficacy of face-to-face delivered CBT on health outcomes in adults over 18 years old with insomnia. Method Relevant randomized controlled trial studies published in the past 22 years were searched through the electronic databases. The PEDro scale was used to assess the quality of the 31 included studies. The mean difference and standard deviation of outcome variables and subgroup variables were analyzed using random effect model and the heterogeneity among the articles were assessed with the Q test and I2. Egger regression analysis was used to assess publication bias. Results The meta-analysis showed a significant reduction in Insomnia Severity Index (standardized mean difference [SMD] = -2.56, 95% CI -3.81 to -1.30, p < 0.001), Pittsburgh Sleep Quality Index (SMD = -0.96, 95% CI -1.25 to -0.68, p < 0.001), sleep onset latency (SMD = -1.31, 95% CI -2.00 to -0.63, p < 0.001), wakening after sleep onset (SMD = -1.44, 95% CI -2.14 to -0.74, p < 0.001), number of awakenings (SMD = -1.18, 95% CI -2.10 to -0.26, p < 0.05), depression (SMD = -1.14, 95% CI -1.85 to -0.42, p < 0.01), and fatigue (SMD = -2.23, 95% CI -3.87 to -0.58, p < 0.01), and a significant increase in total sleep time (SMD = 0.63, 95% CI 0.28 to 0.98, p < 0.001), sleep efficiency (SMD = 1.61, 95% CI 0.92 to 2.29, p < 0.001), and physical health (SMD = 0.42, 95% CI 0.08 to 0.76, p < 0.05), in the CBT intervention group compared with the control group. Conclusion Face-to-face delivered CBT is effective in increasing total sleep time, sleep efficiency, and physical health, and reducing Insomnia Severity Index scores, Pittsburgh Sleep Quality Index scores, sleep onset latency, wakening after sleep onset, number of awakenings, depression, anxiety, and fatigue in patients with insomnia.